2022
DOI: 10.1002/adfm.202110777
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Alternately Layered High‐Loading Film Electrode based on 3D Carbon Nanocoils and PEDOT:PSS for High‐Energy‐Density Supercapacitor

Abstract: The development of flexible carbon‐based film electrodes with high loading and sufficient electron/ion transport channels is of great significance but still challenging. Herein, a flexible high‐loading (over 15 mg cm–2) film with 3D hierarchical pores is prepared by an alternate deposition of carbon nanocoils (CNCs) and poly(3,4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS). The unique alternate architecture of CNC/PEDOT:PSS bilayers possesses porous structure constructed by interconnected CNCs, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 85 publications
0
39
0
Order By: Relevance
“…In addition, Huang et al 127 recently reported a PEDOT:PSS/carbon nanocoils polymer composite to obtain SC electrodes with film‐shaped. The polymer matrix apported mechanical stability while the nanofillers allows the formation of interconnected hierarchical pores, which operate as ions transport channels, shortening the diffusion pathways, and as electrolyte storage reservoir.…”
Section: Polymer and Polymer Composites For Batteries Obtaining And T...mentioning
confidence: 99%
“…In addition, Huang et al 127 recently reported a PEDOT:PSS/carbon nanocoils polymer composite to obtain SC electrodes with film‐shaped. The polymer matrix apported mechanical stability while the nanofillers allows the formation of interconnected hierarchical pores, which operate as ions transport channels, shortening the diffusion pathways, and as electrolyte storage reservoir.…”
Section: Polymer and Polymer Composites For Batteries Obtaining And T...mentioning
confidence: 99%
“…Aiming to develop high‐performance FSCs, exploring novel active materials and electrode structures are two feasible strategies. [ 1 ]…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to develop high-performance FSCs, exploring novel active materials and electrode structures are two feasible strategies. [1] In view of active materials development, heteroatom-doped graphene-like carbon materials stand out from conductive polymers, metal oxides, and other carbon materials due to their 2D plane structures, high surface area, good electrical conductivity, and stability. Moreover, heteroatom-doping can greatly boost the electrochemical properties of graphene-like carbon materials owing to the change of electronic charge density and asymmetric spin density for additional redox reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the kinetic response of most transition-metal compound materials is slow, resulting in a low energy conversion efficiency of the device. Therefore, it is very challenging to construct a high-performance supercapacitor with good electrochemical performance, mechanical flexibility, and stretchability. …”
Section: Introductionmentioning
confidence: 99%